Effet d’incorporation d’écorce de Punica granatum L., sur la qualité d’un lait fermenté type yaourt étuvé - BENDERDOUCH, Mohammed Fethallah; BOUROUBEY, Abdelkader Amine (My University, 2021)
This work dealt with the evaluation of the antimicrobial effect of the hydroethanolic extract of Punica granatum L. on the growth of specific germs and the quality of a fermented milk (yoghurt). The extract of the plant under study was obtained by maceration of a sample of pomegranate peel in a hydroethanolic solution. The extract recovered, after filtration and evaporation, was then incorporated at 0, 2 and 4% in the preparation of a fermented of yoghurt type. The various measurements and evaluations were carried out in triplicate periodically on the 1st, 7th, 14th and 21st day of conservation of the experimental products in the cold at 4°C and concerned: pH, acidity, viscosity, the count of the specific germs of the yoghurt. Organoleptic tests such as taste, adhesiveness, cohesiveness, freshness, color were also performed. The results were subjected to a randomized analysis of variance and a comparison of the means two by two according to the Newman and Keuls test. The addition of hydro ethanol extract of Punica granatum at a dose of 2% seems to maintain the physicochemical and microbiological quality of yoghurts during their cold storage whose acidity, pH, viscosity and even the increase of Streptococcus thermophilus and Lactobacillus bulgaricus germs did not differ significantly from the control. Moreover, the fermented milk with 2% of plant extract enriched with phenolic compounds was as well appreciated by the tasting panel as the control yogurt.
Keywords: Punica granatum, yogurt, hydro ethanol extract, Streptococcus thermophilus, Lactobacillus bulgaricus.